2010
DOI: 10.1242/dev.054130
|View full text |Cite
|
Sign up to set email alerts
|

SoxB1 transcription factors restrict organizer gene expression by repressing multiple events downstream of Wnt signalling

Abstract: SUMMARYFormation of the organizer is one of the most central patterning events in vertebrate development. Organizer-derived signals are responsible for establishing the CNS and patterning the dorsal ventral axis. The mechanisms promoting organizer formation are known to involve cooperation between Nodal and Wnt signalling. However, the organizer forms in a very restricted region, suggesting the presence of mechanisms that repress its formation. Here, we show in zebrafish that the transcription factor Sox3 repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 27 publications
5
39
0
2
Order By: Relevance
“…Our results were over a short time scale so we do not feel that there was likely to be sufficient time for this to occur but it remains formally possible. This is supported by our earlier observations that the repressive effects of the very similar protein, Sox3, were mimicked by an HMG-engrailed repressor fusion protein [22]. …”
Section: Discussionsupporting
confidence: 79%
“…Our results were over a short time scale so we do not feel that there was likely to be sufficient time for this to occur but it remains formally possible. This is supported by our earlier observations that the repressive effects of the very similar protein, Sox3, were mimicked by an HMG-engrailed repressor fusion protein [22]. …”
Section: Discussionsupporting
confidence: 79%
“…However, of these, only Ccnd1, which encodes for the G1/S phase transition licensing factor Cyclin D1, retained its full ability to promote proliferation when coelectroporated with Sox2 ( Figures 3J-3O). In situ hybridization of electroporated E13.5 cortices or chick neural tubes confirmed that the expression level of Ccnd1 was downregulated by Sox2 and upregulated by shRNA-SoxB1 or a dominant-negative variant of Sox3 (Shih et al, 2010) (dnSoxB1; Figures S4B-S4E). In addition, our single-cell analysis also confirmed a strong negative correlation between the expression levels of Sox2 and Ccnd1 (correlation coefficient À0.132) in cortical NPCs under nonoverexpressing physiological conditions ( Figure 3P).…”
Section: Sox2 Represses Genes Promoting Npc Proliferationmentioning
confidence: 79%
“…Second, redundant signaling pathways could function to activate downstream targets of Sox3 and can therefore bypass Sox3. For example, Sox3 has been described as directly controlling Wnt signaling, by inhibiting ␤-catenin expression, in developing zebrafish embryos (50). Third, the progenitor population in young animals and adults may be different and/or contain unique differentiation pathways.…”
Section: Discussionmentioning
confidence: 99%